A dimension formula for reduced plethysms - Alcarás, J.A. Castilho [UNESP]; Tambergs, J.; Krasta, T.; Ruža, J.; Katkevičius, O. (IOP Publishing, 2005)
The boson calculus formalism is used to construct realizations of basis states of irreducible representations of unitary groups taking as a paradigm the interacting boson models of atomic nuclei. These realizations, together with a theorem on plethysms for obtaining branching rules, allowed us to obtain a dimension formula for reduced plethysms. © 2005 IOP Publishing Ltd.